ANALISIS PEMBERIAN REWARD AND PUNISHMENT KEPADA PESERTA DIDIK DI SD INPRES1 BALINGGI - Puspaeni, Ni Luh Dewi; Anta, I Made Nuhari; Sudarsana, Wayan (JATMIKA : Journal Education and Learning of Elementary School, 2024)
This research aims to analyze the provision of rewards and punishment to students at SD Inpres 1 Balinggi. The method used in this research is descriptive qualitative method. The research results obtained through interviews and also using an observation sheet guide show that there are several forms of reward and punishment applied at SD Inpres 1 Balinggi. Forms of reward include: verbal reward (reward in the form of speech) such as "smart", "good job", "correct". Non-verbal rewards such as through body gestures, objects, committee-free awards. The forms of punishment applied at SD Inpres 1 Balinggi include verbal punishment (giving a warning and getting angry only with words), non-verbal punishment (showing an angry face, getting additional assignments). Providing rewards and punishments can have both positive and negative impacts, apart from that it can also have psychological and physical impacts on students.